A study on Problems of Rural Tourism Service Providers in Selected Rural Tourism Destinations in Karnataka, India - Dr. Vikrama D K (Journal of Advanced Zoology, 2023)
Rural tourism is one of the major revenue generation model for rural places in Karnataka. Rural people using tourism as additional revenue generation model along with their main agricultural activities. Now it there is a huge demand from tourists to visit rural tourism destination during weekends and holidays. But the demand also creates lots of problems to rural tourism service providers.